MEDIÇÃO DA MATURIDADE EM GESTÃO DE PROJETOS DE SISTEMAS DE GESTÃO INTEGRADA: UM ESTUDO DE CASO NA ÁREA DE PETRÓLEO E ENERGIA - Ramos, Ana Flávia Batalha (2009)
Project Management provides organizations with a gathering of management processes used to survive in a scenario of great competition and few resources. Due to their complexity, projects for implementing Integrated Management require effective Project Management during all of it´s life cycle. Searching for an increase in Project Management maturity has been a frequent concern of organizations which try to act in a more integrated by providing Project Management culture. In the light of this, it is necessary to choose the option of analyzing Project Management strategies which are innovating and which anticipate market s needs and demands keeping focus on established goals and transforming unexpected in foreseen and monitored risks. The present paper presents concepts that refer to Project Maturity measurement in Integrated Management, seeking to point out all Project Management strategies adopted in the process for implementing this Project.